PENTINGNYA PERAN PEMERINTAH DALAM PELESTARIAN TRADISI PUNGGAHAN - Yanti, Rahmi; Rodiah, Ita (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Punggahan is a traditional welcoming ceremony that takes place before Ramadhan, observed only certain regions, including Koto Rojo in the Muarasipongi district. This tradition is a time-honored practice carried out annually, providing equal standing to all members of the community, regardless of wealth. The aim of this research is to examine the form of government support for the punggahan tradition. A Qualitative methods is employed, utilizing interview with informants that include the district head, community leaders and religious figurers. The Punggahan ceremony begins with a pilgrimage to the graves of ancestors, followed by communal efforts to clean the burial grounds. This is followed by the slaughtering of animals, such as cows or goats, which are cooked together and shared with the entire community.the event concludes with a kenduri (a communal prayer). The local government plays an essential role in the successful execution of the Punggahan tradition, providing both moral and material support, and creating space for the socialization of this tradition to ensure it remains vibrant and is passed down to future generations